Training on Virgin Coconut Oil (VCO) Processing in Banjar Lantangidung, Sukawati District, Gianyar District, Bali - Ni Luh Putu Putri Setianingsih; I Wayan Sudiarta; Dewa Putu Yudi Pardita; Sang Ayu Made Agung Prasetiawati; Gusti Ngurah Oka Jiwantara (Asian Journal of Community Services, 2023)
VCO is a processed food product. One area that processes coconuts into Virgin Coconut Oil (VCO) products is Family Welfare Development (PKK) Br. Lantangidung, Batuan, Sukawati, Gianyar, Bali. PKK Merta Nadi Bro. Lantanidung, Sukawati do not yet have adequate entrepreneurial, production management, or marketing skills. The solution to overcome partner problems is to provide the right technology for VCO processing, equipment assistance, product packaging and labeling knowledge, and marketing. Implementation of community service activities has been running smoothly. The number of participants who took part in this activity was 10. Based on the evaluation results, the group partners mastered VCO processing technology up to 100%. The resulting VCO products are of higher quality, have a longer shelf life, and have a wider market.